2015
DOI: 10.3748/wjg.v21.i16.4946
|View full text |Cite
|
Sign up to set email alerts
|

Biliary drainage strategy of unresectable malignant hilar strictures by computed tomography volumetry

Abstract: AIM:To identify criteria for predicting successful drainage of unresectable malignant hilar biliary strictures (UMHBS) because no ideal strategy currently exists. METHODS:We examined 78 patients with UMHBS who underwent biliary drainage. Drainage was considered effective when the serum bilirubin level decreased by ≥ 50% from the value before stent placement within 2 wk after drainage, without additional intervention. Complications that occurred within 7 d after stent placement were considered as early complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…Management of jaundice and cholangitis caused by MHBO is highly important. However, a consensus regarding the optimal method of drainage for MHBO has not been reached with regard to the drainage area , most suitable type of stent , and stent placement method . In our study, we found that ABBS > 104º and overgrowth were both risk factors for ERI failure after SIS placement.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Management of jaundice and cholangitis caused by MHBO is highly important. However, a consensus regarding the optimal method of drainage for MHBO has not been reached with regard to the drainage area , most suitable type of stent , and stent placement method . In our study, we found that ABBS > 104º and overgrowth were both risk factors for ERI failure after SIS placement.…”
Section: Discussionmentioning
confidence: 69%
“…However, there is still no consensus as to the optimal drainage strategy for treating UMHBO . Generally, bilateral drainage is required when adequate/necessary drainage amounts to >50% of the liver volume . Stent‐in‐stent (SIS) placement or side‐by‐side (SBS) placement are two deployment methods for placement of bilateral SEMSs.…”
Section: Introductionmentioning
confidence: 99%
“…However, this goal usually requires bilateral stenting, increasing the complexity of the procedure. More recently, Takahashi et al showed that a liver volume drainage ≥33% in patients with preserved liver function and ≥50% in patients with impaired liver function correlates with effective biliary drainage in malignant hilar obstruction (130) . Simi larly to distal malignant obstruction, drainage of unresectable hilar tumors should be performed preferably with SEMS, as these stents are associated with prolonged patency.…”
Section: Malignant Biliary Stricturementioning
confidence: 99%
“…They suggested that draining ≥50% of the liver volume, which frequently required bilateral stenting, was a significant predictor of drainage effectiveness in MHBO and a pre-endoscopic retrograde cholangio-pancreatography (ERCP) assessment of hepatic volume distribution of a computed tomography imaging optimized endoscopic procedure. Recently, Takahashi et al [14] examined the liver volume and preserved liver function for effective biliary drainage in UMHBO. They revealed that drainage volume required for effective drainage in UMHBO was ≥33% in patients with normal liver function and ≥50% in patients with impaired liver function (decompensated liver cirrhosis).…”
Section: Drainage Liver Volumementioning
confidence: 99%